2019
DOI: 10.1126/sciadv.aaw9298
|View full text |Cite
|
Sign up to set email alerts
|

Cushing’s syndrome driver mutation disrupts protein kinase A allosteric network, altering both regulation and substrate specificity

Abstract: Genetic alterations in the PRKACA gene coding for the catalytic α subunit of the cAMP-dependent protein kinase A (PKA-C) are linked to cortisol-secreting adrenocortical adenomas, resulting in Cushing’s syndrome. Among those, a single mutation (L205R) has been found in up to 67% of patients. Because the x-ray structures of the wild-type and mutant kinases are essentially identical, the mechanism explaining aberrant function of this mutant remains under active debate. Using NMR spectroscopy, thermodynamics, kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 47 publications
4
99
0
Order By: Relevance
“…Previous studies from our group have shown that PKA-C WT behaves like a K-type enzyme, exhibiting positive binding cooperativity between nucleotide (ATPγN) and pseudo-substrate (PKI 5–24 ). The latter property can be reduced by mutations, while maintaining a virtually constant maximal rate 20 , 23 , 24 . Thus, we sought to understand how this canonical positive binding cooperativity is altered in PKA-C DNAJB1 , using isothermal titration calorimetry (ITC).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies from our group have shown that PKA-C WT behaves like a K-type enzyme, exhibiting positive binding cooperativity between nucleotide (ATPγN) and pseudo-substrate (PKI 5–24 ). The latter property can be reduced by mutations, while maintaining a virtually constant maximal rate 20 , 23 , 24 . Thus, we sought to understand how this canonical positive binding cooperativity is altered in PKA-C DNAJB1 , using isothermal titration calorimetry (ITC).…”
Section: Resultsmentioning
confidence: 99%
“…3a ). These correlations constitute central allosteric nodes necessary for binding cooperativity 18 , 20 , 31 . In addition, allosteric cross-talk exists between residues in the C-terminal tail and residues in the αA-helix (K21, K28), αE-helix (R144, A147, L152), activation loop (R190, V191, G193), and αF-helix (G214, G225).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another mutation leading to Cushing’s syndrome in the Cα subunit of PKA is L205R [ 56 ], which disrupts the intramolecular allosteric network [ 65 ]. Consequently, PKA C L205R has a decreased catalytic efficiency for Kemptide and phosphorylates non-canonical substrates leading to a dysregulated signaling network in tumor cells [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we could subsequently show that PRKACA mutations alter PKA substrate specificity leading to hyperphosphorylation of proteins like histone 1.4, which is implicated in the control of cell proliferation 50 . Furthermore, it has been shown by NMR spectroscopy that the Leu206Arg substitution changes the intramolecular allosteric network in PKA interfering with the normal cooperativity between cAMP and substrate binding 51 . These findings provide a mechanistic explanation for the aberrant activation of PKA caused by PRKACA mutations, and, thus, for the development of cortisol-secreting adrenocortical adenomas in the presence of these mutations.…”
Section: Alterations Of Gpcr Signalling In Endocrine Diseasementioning
confidence: 99%